Pengaruh Edukasi Kesehatan Reproduksi Terhadap Pengetahuan Remaja dalam Pencegahan Kehamilan Remaja - Ariani, Septy; Novianti Syabina, Putri (Pustaka Galeri Mandiri, 2026)
Pregnancy in adolescence can have quite serious psychological impacts, especially due to mental unpreparedness in facing various physical and emotional changes during pregnancy. The role changes that occur also cause their own stress, because many teenagers are not ready to carry out responsibilities as a mother or face the dynamics of household life. Preventing teenage pregnancy is an effective solution to help them be wiser in sexual behavior, avoid sexually transmitted diseases and adopt healthy behaviors. Objective: This study aims to determine the effect of reproductive health education on adolescent knowledge in preventing teenage pregnancy. Method: This study uses a quantitative research method. The design of this study uses a Pretest-Posttest Control Group design. Data collection was carried out using a questionnaire on preventing teenage pregnancy. Results: The results of the study showed that before the intervention,. A total of 105 people (78.4%) were included in the category of poor knowledge, while 29 respondents (21.6%) were in the category of good knowledge. After the intervention, there was an increase. A total of 131 people (97.8%) were included in the category of good knowledge, while 3 respondents (2.2%) were in the category of poor knowledge. The results of the Wilcoxon test showed a p value = 0.000. Conclusion: Based on the research findings, reproductive health education significantly improves adolescents' knowledge of pregnancy prevention. This education also contributes to shaping adolescents' ability to make more informed and healthy decisions.